Enhanced-Mode NiO/Beta-Ga2O3 Heterojunction Field-Effect Transistor: A TCAD Study - Truong, Duc-Minh; Nguyen, Ngoc-Hung; Do, Huy-Binh (Journal of Technical Education Science, 2025)
Ga2O3 is considered to be a promising candidate for the fabrication of high-power semiconductor devices because it has the wide range of band gap from 3.0 eV to 4.9 eV. Because the lack of p-type Ga2O3, p-type NiO/n-type Ga2O3 MOSFETs is expected to realize Ga2O3 power MOSFETs in industry because both Ga2O3 and NiO have wide band gap and high critical electric field. In this work, p-type NiO/n-type Ga2O3 MOSFETs were investigated under the effects of gate-drain distance LGD and acceptor concentration NA in NiO layer, using TCAD simulations. It was found that drain current increases 3 times as the LGD decreases in a range from 8 µm to 1 µm. NA of NiO layer strongly affects the threshold voltage Vth of the devices, illustrating the positive shift of Vth as NA increased from 1.0×1016 cm-3 to 1.0×1020 cm-3. The NiO/Ga2O3 MOSFETs operates in E-mode with Vth > 0 when NA ³ 1.0×1018 cm-3. The change in NA leads to the transformation of NiO/Ga2O3 junction, from a linear-junction (NA = 1.0×1016 cm-3) to an abrupt-junction (NA = 1.0×1020 cm-3). The rise in Schottky barrier within the depletion region at NiO/Ga2O3 junction creates the E-mode of the p-type NiO/n-type Ga2O3 MOSFETs.